The relationship between dietary index for gut microbiota and hyperuricemia: a cross-sectional study using NHANES data - Cai, Xin; Zhang, Shaoqin; Lan, Tianzuo; Jin, Zexu; Liu, Jiajun; Jiang, Zong; Yang, Qingwan (Frontiers in Nutrition, 2025)
BackgroundHyperuricemia (HUA) is a common metabolic disorder, yet the impact of diet and gut microbiota on uric acid metabolism remains insufficiently understood. This study aims to investigate the relationship between the dietary index for gut microbiota (DI-GM) and HUA using data from the National Health and Nutrition Examination Survey (NHANES).MethodsThis study employed NHANES data gathered from 2007 to 2020, encompassing 25,899 adults aged 18 years and older. The DI-GM, which spans from 0 to 14, was calculated based on dietary recall information. The diagnosis of HUA was established through laboratory findings. To examine the relationship between DI-GM and HUA, multivariable logistic regression was utilized, accounting for pertinent confounding variables.ResultsUpon adjusting for possible confounding variables, an elevated DI-GM score demonstrated a notable correlation with a reduced likelihood of HUA [odds ratio (OR) = 0.968, 95% confidence interval (CI) = 0.949–0.987, p = 0.005]. Subjects exhibiting a DI-GM score of ≥6 demonstrated a markedly reduced risk of HUA in contrast to those scoring between 0 and 3 (OR = 0.897, 95% CI = 0.821–0.980, p = 0.016).ConclusionA higher DI-GM score is inversely related to the risk of HUA.